2023
DOI: 10.3390/cells12071029
|View full text |Cite
|
Sign up to set email alerts
|

The TT Genotype of the KIAA1524 rs2278911 Polymorphism Is Associated with Poor Prognosis in Multiple Myeloma

Abstract: Background: The KIAA1524 gene encodes an oncoprotein, CIP2A, which inhibits the phosphorylation of the Akt kinase B, stabilizes the c-Myc protein, and, through that, promotes cancerogenesis. An increase in CIP2A expression has been observed in numerous solid tumors and hematologic malignancies, including multiple myeloma (MM). The aim of our study was to evaluate the clinical impact of the functional single nucleotide polymorphisms (SNP) of the KIAA1524 gene (rs2278911, 686C > T) in MM patients. Methods: Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
(123 reference statements)
0
1
0
Order By: Relevance
“…However, one publication presents the impact of the polymorphism studied on the cachexia risk in patients with gastric cancer (GC) [31]. Our previous study showed the impact of the TT genotype of the KIAA1524 gene (686C>T) on shorter OS in MM patients [32].…”
Section: Introductionmentioning
confidence: 99%
“…However, one publication presents the impact of the polymorphism studied on the cachexia risk in patients with gastric cancer (GC) [31]. Our previous study showed the impact of the TT genotype of the KIAA1524 gene (686C>T) on shorter OS in MM patients [32].…”
Section: Introductionmentioning
confidence: 99%